2021
DOI: 10.1021/acsami.1c09301
|View full text |Cite
|
Sign up to set email alerts
|

Precisely Controlled Synthesis of Hybrid Intermetallic–Metal Nanoparticles for Nitrate Electroreduction

Abstract: Precisely controlled synthesis strategies to prepare anisotropic nanomaterials with high yield and easy operation are exceedingly in demand because hybrid structures often introduce novel properties that cannot be achieved by isotropic nanomaterials. Here, a one-pot, two-step hot injection method was developed to prepare Cu 6 Sn 5 −Sn hybrid intermetallic−metal nanoparticles with an anisotropic structure. Hybrid nanoparticles with distinguishable Sn and Cu 6 Sn 5 domains were formed under mild temperature. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…Due to the sluggish kinetics at low temperature, part of Pt ions involved in the formation of PtSn 4 intermetallic and hybrid PtSn 4 –Sn intermetallic-metal NPs are prepared. Hybrid nanomaterials with an anisotropic structure are attractive materials in many applications such as catalysis, , self-assembly, and cancer therapy …”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Due to the sluggish kinetics at low temperature, part of Pt ions involved in the formation of PtSn 4 intermetallic and hybrid PtSn 4 –Sn intermetallic-metal NPs are prepared. Hybrid nanomaterials with an anisotropic structure are attractive materials in many applications such as catalysis, , self-assembly, and cancer therapy …”
Section: Resultsmentioning
confidence: 64%
“…In the developed galvanic replacement synthetic system, the PtSn 4 intermetallic phase was formed under mild temperatures, from 60 to 120 °C. As shown in Figure 4c nanomaterials with an anisotropic structure are attractive materials in many applications such as catalysis, 30,31 selfassembly, 32 and cancer therapy. 33 To explore the possibilities of synthesizing Pt−Sn nanomaterials with different shapes or intermetallic phases, various Pt to Sn ratios, including 1/10, 1/5, and 1/2, were attempted.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…5,6 Since NO 3 − RR is a multi-electron transfer process involving the generation of diverse byproducts, electrocatalysts with high activity and selectivity are necessary. 7,8 Besides, superior NO 3 − RR kinetics are also required so that to suppress the competing hydrogen evolution reaction (HER). 9 Noble metal-based catalysts, for example, Pt, Ru, and Rh, are demonstrated to show good catalytic activity toward NO 3 − RR, but their widespread applications are hindered by the high cost and competitive HER process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The past several decades have witnessed the application of nanomaterials to many fields of chemistry, especially catalysis. , Nanocatalysts have been reported to exhibit excellent catalytic reactivity and selectivity due to their high surface-to-volume ratio, tunable structure, and high surface reactivity. , The colloidal synthesis of nanoparticles usually requires a capping agent to maintain the nanostructure by binding to metal atoms and minimizing surface energies. Often this capping agent consists of small molecule surface ligands, but polymers such as PVP and PVA can also serve as capping agents. , Dendrimers are a special class of branched polymers that can stabilize nanoparticles and control the precise size control of ultrasmall nanoparticles below 1 nm in size. , In recent years many types of ligands have also been explored, , which help to maintain the nanostructure by binding to metal atoms and minimizing surface energies. ,, Significant effort has been directed toward understanding how these surface ligands influence catalytic performance. It has been shown that ligands can influence catalytic performance through both steric and electronic effects. , Specifically, ligands can sterically constrain a particular conformation for an adsorbed intermediate or block certain reactants from reaching the catalyst surface, thus affecting the activity and selectivity. As an example, it has been shown that chiral ligands can induce enantioselectivity for hydrogenation reactions on metal surfaces by constraining the adsorption geometry of bound intermediates .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Dendrimers are a special class of branched polymers that can stabilize nanoparticles and control the precise size control of ultrasmall nanoparticles below 1 nm in size. 7,8 In recent years many types of ligands have also been explored, 9,10 which help to maintain the nanostructure by binding to metal atoms and minimizing surface energies. 4,11,12 Significant effort has been directed toward understanding how these surface ligands influence catalytic performance.…”
Section: ■ Introductionmentioning
confidence: 99%